Experience of the Orthopedic Surgeon in the Management of War Victims - Almurtadi , Ramzi Ahmad; Farag , Abdalla; Mahmud, Sanad (Al-Mukhtar Journal of Sciences, 2020)
Surgery for victims of war is different from surgery for civilian injuries. War wounds are always extremely contaminated, and missiles may cause massive destruction of soft tissues, bones, and other structures. The principles of surgery for war wounds have been known for decades but need to be relearned by each new generation of surgeons working in a war situation. People were not at all prepared for a physical fight. Similarly, the medical institutes were not specially prepared for such a sea of casualties all of a sudden. The study’s aim was to analyze the result of the experience in the surgical management of the gunshot patients admitted to Al-Bayda teaching hospital during the first month of the Libyan revolution of February 2011. The total number of patients admitted to Al-Bayda teaching hospital in the period from 16\2\2011 to 16\3\2011 was 288 patients. Debridement and repair of the wounds and fixation of fractures in different settings and follow-up was carried out for 7 months. Orthopedic morbidity rate was 9 %, and infection was recorded in 30 patients 21%. As a team of orthopedic, vascular, and general surgeons, very good exposure and experience was gained to manage war or civilian unrest victims.